Concept study of a centralized test facilitz for advancing space food system - Kim, Kyunghwan; Blomqvist, Tor Adrian; Schubert, Daniel (2024)
The resurgence of lunar exploration, led by the International Space Exploration Coordination Group's (ISECG) Global Exploration Roadmap (GER) and NASA’s Artemis missions, has underscored the necessity for sustainable infrastructure to support a long-term human presence on the Moon and Mars. Essential to this endeavor are the advanced technologies required for Life Support Systems, In-Situ Resource Utilization (ISRU), safe habitation modules, etc. A notable development is the bioregenerative life-support system concept of the test facility, called EDEN ISS, conducted in Antarctica from 2015 to 2021. This Mobile Test Facility (MTF) focused mainly on plant cultivation in extreme environments. Current space food research primarily bifurcates into: 1) Earth-produced and processed food that is shipped to space, and 2) Cultivation on-site using space greenhouse-like technologies. Due to resource constraints and food acceptability issues, relying solely on Earth resupply missions is impractical and not always feasible for all mission types. Historical polar exploration cases have shown physical degeneration due to either a lack of or an excess of vitamins and minerals in the diet, some of which were directly related to the state of food preservation at the time, thus highlighting the need for research on food packaging, preservation, and processing in extreme environments. Additionally, there is a conspicuous gap in integrated research addressing the entire chain of space food production, from cultivation to menu development, necessitating a comprehensive approach to space greenhouse technology. This paper introduces a centralized test facility designed to bridge the existing gaps between food cultivation and post-harvest processing to build a sustainable closed-loop cycle of space food research. The objective of this proposed project is to offer a research platform that integrates post-harvest management including packaging, preservation, processing, and controlled environmental agriculture (CEA) systems for global ...